Spawning, larval development and spat settlement of the clam, Meretrix casta (Chemnitz) in the laboratory - Sreenivasan, P V; Rao, K Satyanarayana (Indian Journal of Fisheries, 2011)
The clam, Meretrix casta (Chrannitz) of Family Venwidae, is one of the commercially impOTtant bivalves in India (Al^arswami and Meiyiqjpan 1989). Itiswidelydistributedatong the east and southwest coasts of India and formssustenance fishoy in themmtime states of KamataKa, Kerala, Tamil Nadu and Andhta Pradesh. Besides fishing of Uve cUms, extensive quarrying of sub-fossil cteposits of this species is carried out alcMig the coasts.